NURSING APPROACHES TO PREVENTING HOSPITAL-ACQUIRED INFECTIONS - Gasoon Ahmed Dayea; Nada Hodiri Alshorati; Musab Abdullah Altowairqi; Abdullatif Hedyan Althuwaybi; Fatimah Abdulhadi Aldawood (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Hospital-acquired infections (HAIs) pose a significant threat in healthcare settings, leading to increased morbidity, mortality, and costs. Effective management and prevention of HAIs hinge on the pivotal roles of nursing practices, rigorous education, and robust interdisciplinary collaboration. Nurses, as frontline providers, are integral to enforcing infection control measures such as hand hygiene, proper use of personal protective equipment (PPE), and strict patient-care protocols. Emphasizing the necessity of comprehensive training and continuous education, this abstract highlights how keeping nursing staff well-informed about the latest guidelines and practices is essential for maintaining high standards of infection control. Interdisciplinary collaboration emerges as a fundamental strategy for an all-encompassing approach to managing HAIs, integrating multiple healthcare disciplines. This collaborative effort ensures thorough implementation of both traditional and innovative infection control measures, enhancing their effectiveness and adaptability in response to dynamic healthcare challenges. The culture within healthcare organizations greatly influences the success of infection control efforts. A supportive leadership and a committed culture of safety promote adherence to established protocols and encourage the ongoing adoption of best practices at all staff levels. Conclusively, significant advancements have been made in developing and implementing infection control strategies; however, persistent challenges necessitate relentless commitment and continuous improvement. Ongoing research is vital for refining these strategies, while healthcare leaders must uphold stringent standards of patient safety and care quality. Through dedicated efforts, the frequency and impact of HAIs can be significantly diminished, fostering safer healthcare environments for both patients and professionals.